Liponeurofibroma: Clinicopathological features and histogenesis. Issue 4 (31st January 2018) - Lee, Solam; Bak, Hana; Ahn, Sung Ku
Abstract: A neurofibroma is a common cutaneous benign tumor of neural origin. Various histological variants have been reported. Recently, sporadic reports of fatty variants have been reported but their clinicopathological features have not been well studied. The purpose of this study was to examine liponeurofibroma, and to report the distinctive clinicopathological features and histogenesis in comparison with the classic form. A retrospective study was performed on 130 cases. Immunohistochemical staining was performed for S100, factor VIIIa, perilipin and vascular endothelial growth factor. Masson's trichrome stain was also used. Intratumoral adipocytes were examined with transmission electron microscopy. Thirty‐two (24.6%) cases were classified as liponeurofibroma on microscopic examination. This variant was more common in patients with neurofibromatosis type 1, older age and female sex. The most prevalent location was the head and neck. Intratumoral fat deposits showed differences in morphology and size compared with subcutaneous fat on light microscopy. Neurofibromatosis type 1 had the highest odds of fatty change in liponeurofibroma. In sporadic cases, fatty change can be caused by senescence, chronic injury, or tissue hypoxia secondary to internal or external stimuli. Further investigation is needed to identify the pathomechanism of fatty change in various cutaneous neoplasms, including neurofibroma.